2022
DOI: 10.1088/1361-6668/ac504d
|View full text |Cite
|
Sign up to set email alerts
|

Study of anisotropy in the superconducting properties of FeTe0.55Se0.45 single crystal grown by the self-flux method

Abstract: We report anisotropy in the superconducting properties of FeTe0.55Se0.45 bulk single crystal synthesized via the self-flux method. We have performed magnetotransport, magnetic and heat capacity measurements on single crystals of same batch. The grown crystals have also been characterized by XRD, XPS and Raman measurements. The superconductivity at TC ~ 14 K has been affirmed by the temperature-dependent resistivity, magnetic, and specific heat measurements. The anisotropy in upper critical field (HC2), cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
3
2
0
Order By: Relevance
“…The normalized resistivity / r r T 300 ( ) versus temperature curves, measured in the temperature range 2 K to 300 K in absence of external magnetic field, for all four thin films are shown in figure 5(a). These curves show a sharp transition in resistivity, which is consistent with the other reported results [5,12,40,43,44]. The derivative of normalised resistivity as a function of temperature is presented in the inset of figure 5 c This may be due to the smaller grain-size with weak correlation in F1 [45].…”
Section: Transport Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…The normalized resistivity / r r T 300 ( ) versus temperature curves, measured in the temperature range 2 K to 300 K in absence of external magnetic field, for all four thin films are shown in figure 5(a). These curves show a sharp transition in resistivity, which is consistent with the other reported results [5,12,40,43,44]. The derivative of normalised resistivity as a function of temperature is presented in the inset of figure 5 c This may be due to the smaller grain-size with weak correlation in F1 [45].…”
Section: Transport Propertiessupporting
confidence: 90%
“…It is observed that with increasing the applied magnetic field, the observed T c shifts towards the lower temperatures which is due to the increase in magnetic flux flow in the superconducting transition region. The superconducting transition widths are increasing with the enhancement of applied magnetic field and similar broadening in the resistivity curves has been observed in other IBSs and cuprate superconductors [6,27,40,46]. The relatively small DT c for all the films, even at 12 T indicate their high upper critical fields.…”
Section: Transport Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…This similar response is also observed in other FBSCs. [16,[40][41][42] Below %92 K, we have observed Fermi liquid behavior described by equation ρ ¼ ρ 0 þ AT 2 , where ρ 0 is the residual resistivity and A ¼ 1.98 nΩ cmK À2 . In the inset of Figure 3, the blue line represents the fitting of data showing Fermi liquid behavior in the temperature range 28-92 K. Similar Fermi liquid behavior has also been observed in FBSCs.…”
Section: Transport Propertiesmentioning
confidence: 94%
“…[10][11][12] Also, these FCSs are important for practical applications due to their high H C2 and J C . [13][14][15] The Fe(Te,Se) single crystals exhibit anisotropy in field-dependent transport and magnetic measurements [11,16,17] and the mixed state phenomena for different compositions. [10,[18][19][20] The thermally activated flux flow (TAFF) model has been utilized to study the vortex phase diagram of FBSCs.…”
Section: Introductionmentioning
confidence: 99%